Digital Marketing Socialization for Entrepreneurs in Babakan Banten Village Karawang Regency - Muhamad Dzaki Rusmana; Zalsabilla Ridha Septia; Herlina Putri; Rizki Rifa'i; Rinda Siaga Pangestuti; Husnul Khatimah (Jurnal Pengabdian Masyarakat, 2023)
Purpose: This abstract explores the importance of digital marketing for entrepreneurs in Babakan Banten, emphasizing the need to transition from conventional methods to a digital approach. Method: The study employs presentation-based socialization and Q&A sessions to equip entrepreneurs with digital marketing knowledge and skills, focusing on social media, online shops, and related platforms. Practical Applications: This research aims to equip entrepreneurs with the understanding and practical implementation of digital marketing techniques, including leveraging social media, online shops, and other supporting platforms. Doing so addresses the need to adapt to the business world's digital age. Conclusion: This socialization initiative serves as a bridge to help entrepreneurs in Babakan Banten embrace and apply digital marketing strategies effectively. It offers them the opportunity to harness the power of technology to grow their businesses, showcasing the potential for sustainable growth in a digital era.